Fratrædelsesforelæsning: ANTROPOLOGISKE DILEMMAER: Mellem kulturradikalisme og venstreorientalisme - Liep, John (Tidsskriftet Antropologi, 2018)
This lecture is in three main parts. The first describes the author’s background in a provincial middle class family and the leftish values he absorbed from what is now called “cultural radicalism”. His discontent with his life in urban, capitalist society led him to study anthropology in the belief that “natural” societies of “happiness” could be found far out in the world. The second part briefly characterizes cultural radicalism as a field of progressive intellectual movements in Denmark from the 1920s that fought for the liberation of women, sexuality and the education of children. Danish cultural radicals took an interest in anthropology already during the 30s, when Malinowski’s discovery of free sex in the Trobriands was celebrated, and throughout the 1950s when books by Benedict and Mead on cultural relativity and child training were translated. With the great expansion of the middle class from the 50s the ideas of cultural radicalism deeply changed modern Danish cultural values and institutions. The third part is a critique of what I call “left-wing orientalism”. Cultural relativism was used as a cultural critique of our own society in order to call for reforms. In left-wing orientalism this stance is petrified so that only our society is “wrong” while all the “others” must not be criticized. I discuss three examples of this in anthropology: the general uncritical acceptance of the policies of indigenous movements; the post-colonial “retrospective retouching” of unseemly earlier practices such as cannibalism and, finally, the readiness of anthropologists in Denmark to put the blame for ethnic tensions in the country on the Danes only and their reluctance to take a critical stance to the patriarchal suppression of women and its religious legitimation that young immigrants now themselves speak out against.